Types and Micromorphology of Authigenic Carbonates in the Kolyma Yedoma Ice Complex, Northeast Siberia - Rogov, Victor V.; Kurchatova, Anna N.; Taratunina, Natalia A. (Frontiers in Earth Science, 2021)
The study focuses on authigenic carbonates that are widespread in different deposition environments and are component part of terrestrial biogeochemical cycle of carbon. Samples from the Kolyma Yedoma Ice Complex that formed during the Sartan Cryochrone (MIS 2), the coldest period of the Late Pleistocene, in the northeastern Siberian lowlands, have been studied using scanning electron microscopy and energy-dispersive spectroscopy with replica technique. The samples bear signatures of irreversible multistage cryogenic changes in structure and composition, with formation of authigenic minerals. Authigenic carbonates as secondary phases in the Ice Complex deposits are remarkable by local changes in chemical, physical, and other properties, which induce gradual changes in the lattice and conversion of one mineral species to another. As a result, the sediments may contain stable and metastable minerals. Crystalline species like calcite or aragonite precipitate from aqueous solutions and their presence is restricted to free pore space, in segregation ice. Metastable phases may be produced as an initial reaction product between the CO2 and the aqueous phase, while mineral surfaces and small pores acting as possible nucleation sites. Organic matter is also an important agent in the cryometamorphism of sediments, including precipitation of authigenic phases due to the freezing of colloids and high-molecular compounds.